2023
DOI: 10.1039/d2dt02897b
|View full text |Cite
|
Sign up to set email alerts
|

A multicomponent equimolar proton-conducting quadruple hexagonal perovskite-related oxide system

Abstract: Since the high configurational entropy-driven structural stability of the multicomponent oxide system proposed by Rost et al. in 2015, many experiments and simulations have been done to develop new multicomponent...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…This result undoubtedly shows that the preferentially oriented grains in the {0001} plane have a greater effect on the proton conduction than the Ba nonstoichiometry. As reported in previous work, 42 the sluggishness of the protonation kinetics of BEAZ highlights the need for extended periods of time to stabilize the proton conductivity and emphasizes the importance of carefully considering hydration conditions and sample thickness when studying proton conduction in the BEAZ system (see Figure S15 for hydration time for BEAZ depending on their thickness and sintering temperature). Therefore, in this study, the hydration reaction was carried out for a sufficient period of time, at least for 24 h. A more detailed analysis of the kinetics of proton incorporation will be performed in the future.…”
Section: Anisotropy Of Ion Conduction In Beazsupporting
confidence: 55%
“…This result undoubtedly shows that the preferentially oriented grains in the {0001} plane have a greater effect on the proton conduction than the Ba nonstoichiometry. As reported in previous work, 42 the sluggishness of the protonation kinetics of BEAZ highlights the need for extended periods of time to stabilize the proton conductivity and emphasizes the importance of carefully considering hydration conditions and sample thickness when studying proton conduction in the BEAZ system (see Figure S15 for hydration time for BEAZ depending on their thickness and sintering temperature). Therefore, in this study, the hydration reaction was carried out for a sufficient period of time, at least for 24 h. A more detailed analysis of the kinetics of proton incorporation will be performed in the future.…”
Section: Anisotropy Of Ion Conduction In Beazsupporting
confidence: 55%
“…Later, Youn et al 33 ) have the same crystal structure as Ba 5 Er 2 Al 2 ZrO 13 (10H polytype, hexagonal crystal system, space group P6 3 /mmc) and also exhibit significant proton conductivity. 26,28,30,32,33 In general, a high proton concentration y is required for high proton conductivity. Here, the y values of hydrated perovskitetype BaBO 3−δ and hexagonal perovskite-related oxide Ba Ba 5 A 2 Al 2 ZrO 13 materials are not high due to partial hydration.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Youn et al also showed the anisotropic proton migration in Ba 5 Er 2 Al 2 ZrO 13 experimentally and by density functional theory (DFT) calculations. Ba 5 A 2 Al 2 ZrO 13 -based oxides ( A = Dy, Tm, Yb, Lu, In, Y 1/4 Ho 1/4 Er 1/4 Yb 1/4 , Y 1/5 Dy 1/5 Ho 1/5 Er 1/5 Yb 1/5 , and Y 0.5 In 1.5 ) have the same crystal structure as Ba 5 Er 2 Al 2 ZrO 13 (10H polytype, hexagonal crystal system, space group P 6 3 / mmc ) and also exhibit significant proton conductivity. ,,,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation